Activation of Toll-Like Receptor 9 Impairs Blood Flow Recovery After Hind-Limb Ischemia - Nishimoto, Sachiko; Aini, Kunduziayi; Fukuda, Daiju; Higashikuni, Yasutomi; Tanaka, Kimie; Hirata, Yoichiro; Yagi, Shusuke; Kusunose, Kenya; Yamada, Hirotsugu; Soeki, Takeshi; Shimabukuro, Michio; Sata, Masataka (Frontiers in Cardiovascular Medicine, 2018)
Background; Peripheral artery disease causes significant functional disability and results in impaired quality of life. Ischemic tissue injury releases various endogenous ligands for Toll-like receptors (TLRs), suggesting the involvement of TLRs in blood flow recovery. However, the role of TLR9, which was originally known as a sensor for bacterial DNA, remains unknown. This study investigated the role of TLR9 in blood flow recovery in the ischemic limb using a mouse hind-limb ischemia model. Methods and Results; Unilateral femoral artery ligation was performed in TLR9-deficient (Tlr9-/-) mice and wild-type mice. In wild-type mice, femoral artery ligation significantly increased mRNA expression of TLR9 in the ischemic limb (P < 0.001) and plasma levels of cell-free DNA (cfDNA) as determined by single-stranded DNA (ssDNA) (P < 0.05) and double-stranded DNA (dsDNA) (P < 0.01), which are endogenous ligands for TLR9, compared with the sham-operated group. Laser Doppler perfusion imaging demonstrated significantly improved ratio of blood flow in the ischemic to non-ischemic limb in TLR9-/- mice compared with wild-type mice at 2 weeks after ligation (P < 0.05). Tlr9-/- mice showed increased capillary density and reduced macrophage infiltration in ischemic limb. Genetic deletion of TLR9 reduced the expression of TNF-, and attenuated NF-B activation in ischemic muscle compared with wild-type mice (P < 0.05, respectively) at 3 days after the surgery. ODN1826, a synthetic agonistic oligonucleotide for TLR9, or plasma obtained from mice with ischemic muscle promoted the expression of TNF- in wild-type macrophages (P < 0.05), but not in Tlr9-/- macrophages. ODN1826 also activated NF-B signaling as determined by the degradation of IB in wild-type macrophages (P < 0.05), but not in Tlr9-/- macrophages. In vitro experiments using human umbilical vein endothelial cells demonstrated that TNF-, or conditioned medium obtained from wild-type macrophages treated with ODN1826 accelerated cell death as determined by MTS assay (P < 0.05 and P < 0.01, respectively). Conclusion; Our results suggest that ischemic muscle releases cfDNA, which activates TLR9 and enhances inflammation, leading to impairment of blood flow recovery in the ischemic limb. cfDNA-TLR9 signaling may serve as a potential therapeutic target in ischemic limb disease.